Src inhibitors in the treatment of metastatic bone disease: rationale and clinical data. (December 2011) - Boyce, Brendan; Xing, Lianping
Src is a nonreceptor tyrosine kinase essential for the activation of osteoclasts, the cells that degrade bone. Src also regulates normal cell functions, cancer cell growth and metastasis to organs, including bone where tumor cells induce bone destruction by osteoclasts. Src inhibitors prevent bone destruction and tumor cell growth in animal models of metastatic bone disease, and some are being investigated in clinical trials, particularly in patients with prostate cancer, which has high bone metastatic potential. Here, we review how Src regulates osteoclast formation, activation and survival and the results of preclinical and clinical trials of Src inhibitors, which show some promise in inhibiting the effects of tumor cells on the skeleton.